Multilayered Materials Comprising Mesoporous Thin Films and Metal Nanoparticles - Rodríguez Fernández, Denis; Angelome, Paula Cecilia; Soler Illia, Galo Juan de Avila Arturo; Liz Marzán, Luis M. (Wiley VCH Verlag, 2017)
Fil: Rodríguez Fernández, Denis. BioNanoplasmonics Lab; España